PENGARUH PEMAHAMAN IBU TENTANG PERKEMBANGAN MOTORIK ANAK TERHADAP PERKEMBANGAN MOTORIK ANAK - Ayu Permata; Nova Yulita; Sellia Juwita (LPPM Universitas Abdurrab, 2019)
One of the tasks of parents is to educate children from an early age both in terms of morals, religion, prepare children able to deal with various situations, and educate children to grow and develop optimally. Optimal growth and development in children is the hope of every parent. Achieving optimal growth and development depends on biological potential, the level of achievement of one's biological potential is the result of the interaction of interrelated factors namely genetic, environmental and periaku factors. Toddlers who experience developmental disorders, both fine and rough motor development, hearing loss, lack of intelligence and speech delay. Knowledge and the role of the mother is very beneficial for the overall child development process because parents can immediately recognize the advantages of the child's development process as early as possible separately to be able to provide stimulation to the child's overall growth and development in physical, mental, and social aspects. An understanding of children's growth and development for parents can encourage to develop and learn information in determining educational steps taken to cope with certain situations at the stage of child growth and development. Knowledge about children's growth and development for parents, teachers, and professionals can help to provide educational services optimally. This type of research is field research (field research). The research was carried out on May 7 - June 30, 2018 in Posyandu Dahlia, Aliantan Village, Kabun District, Rokan Hulu Regency, Riau Province. Respondents of this activity are 40 mothers with children ranging in age from 2 months to 5 years in the Dahlia Posyandu, Kabun District, Rokan Hulu Regency, Riau Province. The method that will be used in this research is to use quantitative analysis research methods, namely using in-depth data analysis in the form of data collection methods based on the Questionnaire Method (Questionnaire). The purpose of this research activity is to determine the level of understanding of mothers about the stages of motor development of toddlers at this time and the stages of motor development of toddlers in general. The results of the study are that 40% of mothers do not understand enough about the stages of motor development of children. Based on the results of a survey of respondents, it was found that the respondent conducted a routine examination of the child's growth and development in Posyandu / Hospital routinely, according to the respondents who understood the stages of the child's motor development, but based on the results of the questionnaire assessment of the mother's understanding of the child's motor development stage mother who understands the stage of development of a child's mtoroik. The respondent group needed regular counseling twice a week with guidance from the officers.